Dynamic Compression Simulation of Magnetorheological Elastomer Using Bouc-Wen Hysteretic Model - Jaafar M.F.; Mustapha F.; Mustapha M. (Trans Tech Publications Ltd, 2024)
This paper explores the versatility of the Bouc-Wen hysteresis model in simulating the dynamic behaviour of magnetorheological elastomer (MRE) material. The Bouc-Wen model has been used in many fields of science including modelling the hysteresis phenomenon that happens in magnetic material, elastomer, base isolation of structures and many more. Introduced by Robert Bouc, this nonlinear hysteretic model has been modified by many researchers to suit different applications. Compression testing of MRE material under high strain amplitude produces a nonlinear hysteresiscurve based on stress-strain data. Bouc-Wen hysteretic model can simulate the hysteresis curve of MRE material using the parameter identification method within MATLAB Simulink. This work has shown that the seven Bouc-Wen parameters can be optimized using the parameter identification method and it is found that the model can predict the output force with a residual of less than 18%. 2023 Trans Tech Publications Ltd, Switzerland.